Considerations of growth factor and material use in bone tissue engineering using biodegradable scaffolds in vitro and in vivo - Karen M. Marshall; Jonathan P. Wojciechowski; Vineetha Jayawarna; Abshar Hasan; Cécile Echalier; Øystein Øvrebø; Tao Yang; Kun Zhou; Janos M. Kanczler; Alvaro Mata; Manuel Salmeron-Sanchez; Molly M. Stevens; et al. (Scientific Reports)
Abstract Bone tissue engineering aims to harness materials to develop functional bone tissue to heal ‘critical-sized’ bone defects. This study examined a robust, coated poly(caprolactone) trimethacrylate (PCL-TMA) 3D-printable scaffold designed to augment bone formation. Following optimisation of the coatings, three bioactive coatings were examined, i) elastin-like polypeptide (ELP), ii) poly(ethyl acrylate) (PEA), fibronectin (FN) and bone morphogenetic protein-2 (BMP-2) applied sequentially (PEA/FN/BMP-2) and iii) both ELP and PEA/FN/BMP-2 coatings applied concurrently. The scaffold material was robust and showed biodegradability. The coatings demonstrated a significant (p < 0.05) osteogenic response in vitro in alkaline phosphatase gene upregulation and alkaline phosphatase production. The PCL-TMA scaffold and coatings supported angiogenesis and displayed excellent biocompatibility following evaluation on the chorioallantoic membrane assay. No significant (p < 0.05) heterotopic bone formed on the scaffolds within a murine subcutaneous implantation model, compared to the positive control of BMP-2 loaded collagen sponge following examination by micro-computed tomography or histology. The current studies demonstrate a range of innovative coated scaffold constructs with in vitro efficacy and clearly illustrate the importance of an appropriate in vivo environment to validate in vitro functionality prior to scale up and preclinical application.